Avaliação da reciclagem de lodo de tratamentos de água na produção de blocos de cerâmica vermelha - Bandieira, Mariana (2021)
The most used water treatment in Brazil is through conventional water treatment plants (WTPs). The process seeks to make drinking water suitable for human consumption, and it is essential to remove suspended solids from the water to achieve potability parameters. In this process, a waste solid named sludge is generated, where it is estimated that a conventional WTP generates a sludge of 2.5% of the volume of treated water. Raw water in a treatment plant goes through the processes of capture, coagulation, flocculation, decantation or flotation and filtration, with the sludge being formed and accumulated in these last three stages. Currently, the WTPs is classified by NBR 10004/2004 as a class II-A solid waste, non-inert and non-hazardous, and must be disposed in an appropriate place, in compliance with environmental legislation. However, the methods and techniques available for this are costly and require adequate logistics for transport. In this sense, studies were conducted seeking to re-use sludge as a raw material in civil construction, such as for the manufacture of concrete, mortar, among others. However, the processing necessary for the dehydration of the sludge and its insertion in these productive sectors makes its use economically unfeasible. In this scenario, this project aims to evaluate the effect, as well as the technical feasibility of replacing sludge from a water treatment plant on the physicochemical and mechanical properties of red ceramic products. For this, the experimental procedure was developed into three stages: the first, where the physical, chemical and mineralogical characterization tests of the materials used (clay and sludge). In the second stage, the production process of extrusion of bricks was evaluated by consistency and plasticity tests. Data obtained through rheological tests were correlated, with different levels of sludge and moisture, adjusting the traces in order to promote a linear extrusion, without surface defects in the bricks produced. Ceramic bricks were manufactured on a reduced scale, with different sludge replacement contents (2, 5, 10 and 20% in clay replacement) and submitted to the same parameters during the molding, forming, drying and firing process. The physical and mechanical properties required by NBR 15270/2017 were evaluated. In this sense, the research sought to technically enable the use of WTS sludge for the manufacture of ceramic products. Through the optimization of the production process, it was possible to conclude that bricks produced with sludge contents below 5% has significant potential for its use, as long as there is a moisture control in the green clay paste, as well as in the burning drying process.